EXPLORING SIMILARITIES IN MEDICAL ETHICS BETWEEN JAPAN AND UZBEKISTAN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Medical ethics is essential in healthcare systems around the world, guiding healthcare professionals to follow moral standards when caring for patients. This paper explores the fascinating similarities in medical ethics and doctor-patient interactions between Japan and Uzbekistan. It looks at how cultural and historical influences shape the way healthcare professionals approach sensitive matters, such as involving families in difficult medical decisions. The focus is on the shared ethical principles guiding doctors in both countries, revealing common practices in patient care.